Sanitation service management and its impact on citizen satisfaction, Municipality of Pichari, 2022 - Hinostroza Villafuerte, Omar (2025)
The main objective of this research is to determine how sanitation service management impacts citizen satisfaction in the Municipality of Pichari (2022), within a development time of 1 year and 3 months. In terms of methodology, the research is applied, with a quantitative approach by level or scope, descriptive and correlational, with a non-experimental, cross-sectional design and a deductive method. In terms of technique, a survey was used, with a questionnaire as the instrument, which was validated by three experts in the field and applied to a sample of 75 employees of the Municipality of Pichari, selected from a population of 330, during the months of October and November 2022. The questionnaire consists of 40 questions, with five optional response alternatives, according to the Likert scale. Likewise, the reliability of the instrument was calculated using IBM's SPSS statistical program, version 29, finding that Cronbach's alpha coefficient was 0.916, a value that indicates that the instrument is highly reliable. Finally, a correlation analysis was performed between the variables, revealing a strong relationship between sanitation service management and citizen satisfaction, with a Spearman correlation value of 0.773, which implies that the variables under analysis have a high correlation.